USING INTRAPERSONAL INTELLIGENCE IN IMPROVING STUDENTS ABILITY TO WRITE DESCRIPTIVE PARAGRAPH OF EIGHTH GRADE STUDENTS AT SMP MUHAMMADIYAH SUMBERHARTA - Yulfi Yulfi; Syaprizal Syaprizal; novita sari (Journal of English Education, Literature and Linguistics, 2020)
The problem of this study was “is it significantly effective to use Intrapersonal Intelligence strategy in improving students’ ability to write descriptive paragraph to Eighth grade students at SMP Muhammadiyah Sumberharta in academic year 2019/2020?”. The objective of this study was to find out whether or not it was significantly effective to use Intrapersonal Intelligence strategy in teaching writing descriptive paragraph to Eighth grade students of SMP Muhammadiyah Sumberharta in academic year 2019/2020. The population of this study was all of the eighth grade students of SMP Muhammadiyah Sumberharta in academic year 2019/2020 and total number of sample was 21 students from VIII.B. The sample in this study was taken through cluster random sampling. In this study, the writer used pre-experimental method. In collecting the data, the writer used written test. In analyzing the data, the writer used two techniques, individual students’ score and paired t-test. Based on the result of the data analysis, the writer found out that the students’ average score was 67.29 in the pre-test and it increased in the post-test which score was 77.80. The result of paired t-test was 5.20 while ttable was 1.725. It means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Furthermore, it was significantly effective to use Intrapersonal Intelligence strategy in improving students’ ability to write descriptive paragraph to the Eight grade students at SMP Muhammadiyah Sumberharta in academic year 2019/2020.